ANALISIS EFEKTIVITAS TERAPI ANTIRETROVIRAL PADA PASIEN HIV/AIDS RAWAT JALANDI RSUP FATMAWATI JAKARTA TAHUN 2016 - Yusi Anggriani; Alfina Rianti; Jenny Pontoan; Yulwa Juwita (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2019)
The increasing of HIV/AIDS every year become a health problem in Indonesia. Patients of HIV/AIDS should use longterm Antiretroviral (ARV) therapy of antiretroviral therapy to support the success of antiretroviral therapy. The objective of this study was to know and compare the effectivity of four ARV combination. The four ARV combination are combination A (AZT+3TC+NVP), combination B (AZT+3TC+EFV), combination C (TNF+3TC+NVP), combination D (TNF+3TC+EFV) base on increasing CD4. This study cohort-longitudinal design. Samples for this study were taken by total sampling using all data of HIV/AIDS outpatients at RS Fartmawati on 2016. The inclusion criteria were patients of (≥17 years old), received treatment of either one of the four ARV combination, and had data of CD4 from laboratory result before and 6-12 months after the treatment. Data were taken from patients medical record and analyzed with non-parametric Kruskal Wallis-test. The study results showed of 124 patients had increased the CD4 mean >100 sel/mm3 one year after the treatment. The average rate of increment of each combination of antiretroviral therapy on a median CD4 cell count of 1 year was a combination of A (73.93), combination B (70.87), combination C (48.73), combination D (55.57) and there was a significant difference in CD4 cell gain in patients taking combination A-C (p value = 0.047), combination A-D (p value = 0.041), and combination B-D (p value = 0.045) at the evaluation on 1 year. Conclusion, combination A is more effective than combination B, D and C.